The application of novel boron complexes in asymmetric transfer hydrogenation of aromatic ketones. Issue 18 (15th October 2015) - Temel, Hamdi; Paşa, Salih; Aydemir, Murat
Graphical abstract: Abstract: Asymmetric transfer hydrogenation using iso -PrOH as a hydrogen source offers an attractive route for reducing simple unsymmetrical functionalized ketones to chiral alcohols. The combined use of organometallic and coordination chemistry has produced a number of new and powerful synthetic methods for important classes of compounds in general and for optically active substances in particular. For this aim, the ( S, Z )-1-((1-hydroxy butane-2-yl imino)methyl)naphthalene-2-ol chiral ligand was chosen to obtain boron complexes. Boronic derivative compounds such as phenylboronic acid, 6-methoxynaphthalen-2-ylboronic acid, 4-methyl-3-nitrophenylboronic acid and 1, 4-phenylenediboronic acid were applied to obtain complexation with chiral based ligands. The structures of these ligands and their complexes have been elucidated by a combination of multinuclear NMR spectroscopy, LC–MS/MS, TGA/DTA, UV–Vis., elemental analysis, XRD, SEM, and FTIR. These boron complexes have also been tested as catalysts in the enantioselective transfer hydrogenation of acetophenone derivatives to afford the corresponding product, ( S )-1-phenylethanol with high conversions (up to 99%) and modest enantioselectivities (up to 70% ee). The substituents on the backbone of the ligands had a significant effect on both the activity and % ee. Abstract : ( S, Z )-1-((1-Hydroxy butan-2-ylimino)methyl)naphthalen-2-ol: C15 H17 NO2 [ α ]D 20 = −11.9 ( c 0.5, DMSO) Source of chirality: ( S )-2-aminobutan-1-ol Absolute configuration: ( S ) Abstract : ( S, Z )-5-Ethyl-2-phenyl-4, 5-dihydronaphtho[2, 3- h ][1, 3, 6, 2]dioxazaboronine: C21 H20 BNO2 [ α ]D 20 = +1.5 ( c 0.5, DMSO) Source of chirality: ( S )-2-aminobutan-1-ol Absolute configuration: ( S ) Abstract : ( S, Z )-3-Ethyl-6-(6-methoxynaphthalen-2-yl)-3, 4-dihydronaphtho[1, 2- h ][1, 3, 6, 2]dioxazaboronine: C26 H24 BNO3 [ α ]D 20 = −3.5 ( c 0.5, DMSO) Source of chirality: ( S )-2-aminobutan-1-ol Absolute configuration: ( S ) Abstract : 1, 4-Bis(( S, E )-5-ethyl-4, 5-dihydronaphtho[2, 3- h ][1, 3, 6, 2]dioxazaboronin-2-yl)benzene: C36 H34 B2 N2 O4 [ α ]D 20 = −10.6 ( c 1, DMSO), Source of chirality: ( S )-2-aminobutan-1-ol Absolute configuration: ( S, S ) Abstract : ( S, Z )-5-Ethyl-2-(4-methyl-3-nitrophenyl)-4, 5-dihydronaphtho[2, 3- h ][1, 3, 6, 2]dioxazaboronine: C22 H21 BN2 O4 [ α ]D 20 = −6.7 ( c 0.5, DMSO) Source of chirality: ( S )-1-amino-2-propanol Absolute configuration: ( S )